PENGARUH SUNMORI TERHADAP PENGEMBANGAN WISATA MINAT KHUSUS DI BUKIT NIPAH - Muhammad Syahroni Ramadhan; I Made Murdana; Uwi Martayadi (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
The success of the most popular motorcycle racing event in the world that is WSBK and MotoGP wich held at Pertamina Mandalika Circuit, made Lombok visited by a lot of motorcycle communities who did touring, not only touring activities that were often caried out by the motorcycle community were sunmori. Sunmori has become a very popular in the last couple year, one of the most popular sunmori location in Lombok is Bukit Nipah. The purpose of this research is to find out influence of sunmori of the development special interest tours in Bukit Nipah. The population in this research is a biker community who carry out sunmori activities in Bukit Nipah. The sampling technique used is Insidental Sampling and data collection technique by observation, interview, documentation and using a questionnare to 30 respondents. The data was analyzed using simple linear regression, determinant coefficient test (r2), and t test. The research result indicate that sunmori has a positive effect on the development of special interest tours in Bukit Nipah with a percentage of 69,5%, while 30,5% is influenced by other variabels that has not been researched on this paper.